Estudo comparativo da expressão da proteína caspase 3 clivada em hiperplasias fibrosas inflamatórias, lesões cancerizáveis e carcinomas de células escamosas bucais - Leite, Ana Flávia Schueler de Assupção (2007)
Apoptosis is a type of programmed cellular death genetically related to both physiological and pathological conditions and even related to etiopathogenesis of potentially cancerous and neoplasic conditions. Mutations and molecular alterations avoiding physiological apoptosis are related to oral carcinogenesis. The characteristics events of apoptosis involve activation of a protease protein family known as caspases. Within this family, caspase 3 is considered the main effector caspase of the apoptosis cascade and its expression has being studied in many malignant neoplasia.This work aimed the evaluation of apoptosis, through cleaved caspase 3 detection, in hyperplastic, potentially cancerous and both lower lip and intraoral carcinoma lesions. We selected 20 paraffin blocks from each lesion group: intraoral and labial fibrous inflammatory hyperplasia, actinic cheilitis, oral leukoplakias with and without epithelial dysplasia and intraoral/lower lip squamous cell carcinoma, thus making a total of 120 blocks. One section of each block was used for immunohistochemical detection of caspase 3 with anti-cleaved caspase 3 antibody (Asp 175#9661 Cell Signaling Technology). Hematoxilin & Eosin slides were described under light microscopy. Immunohistochemical results were analyzed both descriptive and quantitatively with Image Pro Plus 4.5 software. Aiming to confirm immunohistochemical results, twenty-two samples were selected to for another apoptotic cell detection technique: TUNEL (Kit ApopTag Plus Peroxidase In situ Apoptosis Detection S7101 - Chemicon International). Area density was correlated with behavior of studied lesions. Oral squamous cell carcinomas presented area density greater than other lesions and premalignant lesions had area density higher than hyperplasias, although this was no statistically significant. Positive cells in hyperplastic lesions were rarely detected. Carcinomas of the lower lip, which are characterized by slower evolution and low recidive rate, had lower area density than intra-oral samples. Actinic cheilitis without evidence of epithelial dysplasia presented area density higher than epithelial dysplastic lesions, thus supporting the role of apoptosis, inducing by solar ultraviolet radiation, as protecting factor in those lesions before morphological alterations of epithelial dysplasia take place. Inversely, all leukoplakia samples with epithelial dysplasia were positive for cleaved caspase 3. Most of leukoplakias and actinic cheilitis that exhibited lichenoid reaction presented greater area density when compared to the others. We observed TUNEL positive-cells in terminally differentiated keratinocytes, below the hyperkeratotic band where cleaved caspase 3 positivity was not observed, thus suggesting that terminal differentiation in oral epithelium does not represent classical apoptosis. Cleaved caspase 3 expression represents a reliable method for apoptosis detection in histological sections of archival paraffin-embedded material. However, more studies to verify the correlation of cleaved caspase 3 expression with clinical and histopathological characteristics of squamous cell carcinoma, anticancer therapy, prognostic and survival index and its association with other methods of identification of apoptosis can still aid more knowledge of the ethiopathogenesis of those lesions, therefore improving treatment and prognostic